Mobile Forensic for Body Shaming Investigation Using Association of Chief Police Officers Framework - Yana Safitri; Imam Riadi; Sunardi Sunardi (Universitas Bumigora, 2023)
Body shaming is the act of making fun of or embarrassing someone because of their appearance, including the shape or form of their body. Body shaming can occur directly or indirectly. MOBILEdit Forensic Express and Forensic ToolKit (FTK) Imager are used to perform testing of evidence gathered through Chat, User ID, Data Deletion, and Groups based on digital data obtained on IMO Messenger tokens on Android smartphones. This study aimed to collect evidence of conversations in body shaming cases using the Association of Chiefs of Police (ACPO) framework with MOBILedit Forensic Express and FTK Imager as a tool for testing. Based on the research findings, MOBILedit Forensic Express got an extraction yield of 0.75%. In contrast, using the FTK Imager got an extraction yield of 0.25%. The ACPO framework can be used to investigate cases of body shaming using mobile forensics tools so that the extraction results can be found. The results of this study contributed to forensic mobile knowledge in cases of body shaming or cyberbullying ACPO framework as well as for the investigators.